The clinical effect of tendon repair for tendon spontaneous rupture after corticosteroid injection in hands: A retrospective observational study. Issue 41 (October 2016) - Lu, Hui; Yang, Hu; Shen, Hui; Ye, Ganmin; Lin, Xiang-Jin
Abstract : Abstract: Corticosteroid injections for hand tendinitis can lead to a rare significant complication of tendon spontaneous rupture. However, only sporadic cases were reported in the literature before. This study was designed to gauge the clinical effect of tendon repair in patients of tendon spontaneous rupture after corticosteroid injection and analyze our experience. This was a retrospective observational study of 13 patients (8 women and 5 men) operated between July 2011 and December 2015 for tendon spontaneous rupture after corticosteroid injection. Demographic data, clinical features, imaging data, and surgical treatments were carefully reviewed. The average age was 52.308 ± 15.381 years (range 29–71). The average injection times were 2.538 ± 1.664 times (range 1–6). The average rupture time (after last injection) was 10.923 ± 9.500 weeks (range 3–32). Nine patients were treated by tendon suture (69% of cases), and 4 patients were treated by tendon grafting (31% of cases). All patients received follow-up in our outpatient clinic. The sites of the tendon rupture (15 tendons of 13 patients had involved) include extensor pollicis longus (6 tendons, 40% of cases), extensor digiti quinti and extensor digiti minimi (4 tendons, 27% of cases), ring finger of extensor digitorum communis (3 tendons, 20% of cases), and middle finger of extensor digitorum communis (2 tendons, 13% of cases). Two patients who had tendon adhesion (15% of cases) were treated by tendon release. One patient who had tendon rerupture (8% of cases) was treated by tendon grafting. No patient had complications of infections, vascular, or nerve injury. Tendon spontaneous rupture is a serious complication after corticosteroid injection for tendinitis. Rigid standard of corticosteroid injection is very important. Magnetic resonance imaging was contributory to preoperative assess tendon defect and can be used to monitor healing quality of tendons during the follow-up.